Clinical Characteristics, Acute Complications, and Neurologic Outcomes of Salmonella Meningitis in Saudi Infants and Children - Alsubaie, Sarah; Alrabiaah, Abdulkarim (Journal of Pediatric Infectious Diseases, 2020)
Objective This study aimed to clarify the clinical presentations, acute complications, and long-term sequelae of Salmonella meningitis in Saudi infants and children.Methods This retrospective study, conducted from 1999 to 2016, evaluated the neurological complications and long-term outcomes of children 14 years of age and younger diagnosed with Salmonella meningitis at King Khalid University Hospital. All affected children had 3 years of follow-up to assess neurologic complications and mortality.Results Invasive Salmonella infection occurred in 141 patients. Of those, 14 (10%) had meningitis. The median age of onset of infection was 4.7 months. The most frequent symptoms at presentation included fever (100%), seizures (71%), diarrhea, and vomiting (43%). Nontyphoidal Salmonella species were isolated in all (but one) cerebrospinal fluid samples. Relapse occurred in four patients owing to inadequate antibiotic duration, although the organisms were susceptible to ceftriaxone. The majority of patients (86%) developed acute neurologic complications, including subdural empyema and multiple cerebral infarcts (57%), hydrocephalus (36%), ventriculitis (29%), and cerebral venous sinus thrombosis (21%). Four patients (28.5%) died due to Salmonella meningitis complications. Four patients survived with full recovery. Six patients (60%) had long-term neurologic complications. Hydrocephalus, cerebral palsy, developmental delay, and epilepsy occurred in five, four, three, and three patients, respectively.Conclusion Salmonella meningitis results in significant mortality and adverse neurodevelopmental outcomes. The probability of relapse after an apparent recovery should be considered. Consensus on antibiotic treatment for Salmonella meningitis is needed.
Keywords: Salmonella; meningitis; children; infants